The application of information success model in Perpustakaan Tun Abdul Razak (PTAR) UiTM / Noor Azlin Abdullah and Safawi Abdul Rahman. - Abdullah, Noor Azlin; Abdul Rahman, Safawi (Perpustakaan Tun Abdul Razak (PTAR), 2021)
Information and Communications Technology (ICT) and Internet have changed the way organizations deliver services. Using ICT and Internet technology, organizations can deliver digital services to consumers quickly and effectively. In the context of libraries and digital libraries, service delivery has been greatly improved along with the extensive use of ICT and Internet in the library. This paper discusses the delivery of digital library services at UiTM’s Tun Abdul Razak Library (PTAR) with reference to the Information System Success Model introduced by Delone & Mclane. PTAR digital library initiatives such as MyKnowledge Portal, CHAT WITH LIBRARIAN, E-Class Information Skills (eKKM) are discussed by mapping them with service quality (SQ), Information Quality and System Quality elements in the IS Success Model. As a result, from the context of the use of the system as a service delivery platform, the implementation of PTAR digital initiative is found to be aligned with IS Success Model.